THE PREVAILING SCIENTIFIC VALUES IN CHILDREN’S PROGRAMS PROVIDED BY MBC3 - Mohammed, Seeinhat (ALBAHITH ALALAMI, 2020)
The main problem of this research titled (the prevailing scientific values in children’s programs provided by the channel (mbc3) is the disclosure of the scientific values that are included in the children’s program in the mbc3 channel) which are directed to an important group of society, which is the category of children who spend long hours in front of TV screens to watch these programs, and therefore they acquire many values that can replace fixed values, such as social, moral, religious, etc., and the content analysis method has been used to analyze children’s programs presented by mbc3 channel), and the research has reached a number of The results can be summarized b To come: *The degree of importance of the scientific values varied in the mbc3 channel, so my values were to learn new skills and gain, and the values of understanding and thinking are repetitions and the higher ratios among other categories of scientific values .. *Children’s programs increase the child’s culture through the abundant information contained in the contents of children’s programs in the channel (mbc3). *The main scientific value group of MBC3 has three values: values of culture, values of knowledge, and values of understanding and thinking. *The values of acquiring or learning new skills had the highest percentage in the set of sub-values for the values of culture, while the value of information reached the highest value in the set of knowledge values, and finally the value of the urge to think formed the highest percentage in the set of sub-values for the values of understanding and thinking. *The characters embodied for the value were in the channel (mbc3), in the category of cartoon characters and adults only * The category of cartoon characters formed the highest percentage of cultural values among the categories of persons embodying the value, while the category of adults was the highest in the values of understanding and thought within the group of the main scientific values in the mbc3 channel.